(untitled) (International Current Pharmaceutical Journal, 2013)
The objective of this study was to develop mucoadhesive tablets of Simvastatin using natural polymers. Simvastatin has short biological half-life and high first pass metabolism hence which was designed to increase the gastric residence time which prolong the drug release. The tablets were prepared by wet granulation technique using Carbopol-934, guar gum, xanthine gum and chitosin as polymers. Formulations were evaluated for different parameters like hardness, friability, uniformity of weight, swelling characteristics, in vitro dissolution and kinetic studies. The dissolution was carried out for 12 hours in which the formulation with guar gum has shown highest dissolution release profile (F9). Thus the present study concludes that mucoadhesive tablets of simvastatin can be a good way to pass the extensive hepatic first pass metabolism and to improve the bioavailability of simvastatin. DOI: http://dx.doi.org/10.3329/icpj.v2i9.16077 International Current Pharmaceutical Journal, August 2013, 2(9): 152-155